2014
DOI: 10.1080/10498850.2013.791740
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Protein Hydrolysate Obtained from OysterSaccostrea cucullata(Born, 1778)

Abstract: The antioxidant activities of enzymatically hydrolyzed (protease from Bacillus cereus SU12) oyster (Saccostrea cucullata) protein were studied. The hydrolysate exhibited a strong antioxidant potential in 1, 1-diphenyl-2-picrylhydrazyl (DPPH, 85.7 ± 0.37%), followed by hydrogen peroxide radical scavenging activity (81.6 ± 0.3%), hydroxyl radical scavenging activity (79.32 ± 0.6%), and reducing power assay (2.63 ± 0.2 OD at 700 nm) at a concentration of 1 mg/mL. Due to the high antioxidant potential, the hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Similarly to our result, the protein hydrolysate obtained from the oyster Saccostrea cucullata exhibited 85.7% [10], the hydrolysate of the common smooth hound (Mustelus mustelus) exhibited 76.7% of scavenging activity [36], and protein hydrolysate of Conus betulinus exhibited 84% of scavenging activity [37]. By comparing the percentage of radical scavenging activity, the acid and enzymatic hydrolysates have proven to be a potential source for antiradical activity.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly to our result, the protein hydrolysate obtained from the oyster Saccostrea cucullata exhibited 85.7% [10], the hydrolysate of the common smooth hound (Mustelus mustelus) exhibited 76.7% of scavenging activity [36], and protein hydrolysate of Conus betulinus exhibited 84% of scavenging activity [37]. By comparing the percentage of radical scavenging activity, the acid and enzymatic hydrolysates have proven to be a potential source for antiradical activity.…”
Section: Resultssupporting
confidence: 85%
“…At the same time, raw materials of animal-including marine-origin, and products (of animal/marine origin) that have been subjected to technological and biotechnological modification could also have antioxidants. The biological and pharmacological activities of organic natural compounds of marine origin have been demonstrated by numerous studies [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Umayaparvathi et al . (2014) found that oyster protein hydrolysates have potent antioxidant properties; the results are similar to Dong et al . (2010).…”
Section: Introductionsupporting
confidence: 81%
“…Possible bioactivities of oyster peptides have been reported. Umayaparvathi et al (2014) found that oyster protein hydrolysates have potent antioxidant properties; the results are similar to Dong et al (2010). Cheng et al (2018) discovered a new anticoagulant peptide that could potently prolong the activated partial thromboplastin time and the thrombin time, and this peptide was purified and identified from the pepsin hydrolysate of oyster.…”
Section: Introductionmentioning
confidence: 66%
“…Moreover, F5 possessed high DPPH, hydroxyl, and superoxide radical-scavenging activities of 90.16%, 81.15 U/ml, and 108.20 U/g at 1 mg/ml, respectively, with similar activities not achieved by the other peptides. In contrast, the DPPH radical-scavenging activity of the peptide from S. cucullata at 1 mg/ml was only 85.7% (Umayaparvathi et al, 2015).…”
Section: Discussionmentioning
confidence: 82%